Study the Impact of Laser Energy on Laser-Induced Copper Plasma Parameters By Spectroscopic Analysis Technique - Ibrahim Karim Abbas (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
In this paper, spectroscopic analysis (OES) for copper (Cu) plasma was achieved at atmospheric pressure. Q switched Nd: YAG pulsed laser with a fundamental wavelength (1064 nm), energy range (500-800) mJ, frequency (6 Hz), and laser pulses (10-30 pulses) was applied to induce copper plasma. Based on the spectroscopic analysis, plasma parameters like electron temperature (Te), electron density (ne), Debye length (λD), and plasma frequency (fp) have been calculated. The results demonstrated that the laser energy affects all plasma parameters, with an electron temperature (Te) range of (0.6820-0.8949) eV and electron number density (ne) range of (13.667-17.235)×1017 cm−3. Also, the image of the place of laser bombardment of copper (Cu) metal shows three diameters or circles, each circle bears a different color from the other. It can be described as a crater, and the interaction of the laser with copper metal is obvious by laser ablation, and here the effect of the increased energy of the laser appears during the spectroscopic diagnosis and the process of metal bombardment.